Analysis of the Background of the Problems of Article 50B Paragraph 2 (C) of the Revision of the Broadcasting Law 2024 in the Perspective of Democratic Resilience - Hendra Pakpahan; Palupi Lindiasari Samputra; Margaretha Hanita (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
The revision of the Broadcasting Law 2024, particularly Article 50B paragraph 2Â  (c) which prohibits the "exclusive investigative journalism," has sparked controversy among media and democracy stakeholders in Indonesia. This study aims to (1) analyze stakeholders' perspectives on this provision, (2) examine the differences and similarities in perspectives in the context of democratic resilience, and (3) synthesize the underlying issues to provide recommendations for strengthening democracy. Grounded inÂ  democracy theories, this research adopts a qualitative approach using document studies from national media sources and official documents between May and November 2024. The data is analyzed using assumption analysis to identify stakeholder perspectives. The findings reveal a polarization between policymakers, who emphasize restrictions as a protective tool, and the press, which perceives them as a threat to freedom. However, a consensus emerges on the need for clearer media regulation and the protection of public interests. From a democratic resilience perspective, the macro-institutional level is identified as the weakest due to regulatory ambiguity and overlapping institutional authority, which may undermine democratic oversight and impede media control functions. The study concludes that Article 50B paragraph 2 (c) of the Broadcasting Act has the potential to threaten democratic sustainability. It therefore recommends a reassessment of the law and the article, as well as strengthening institutional coordination to harmonize regulations.